Environmental evaluation study of toxic elements (F, Zn, Be, Ni, Ba, U) in the underground coal gasification (UCG) residuals. (15th May 2021) - Ma, Weiping; Li, Zhen; Lv, Jiafeng; Yang, Lanhe; Liu, Shuqin
Abstract: Underground coal gasification (UCG) is considered to be an important means of coal utilization. However, the stability of underground coal gasification residuals has always been the focus of people's attention. In this paper, based on the sequential chemical extraction and thermodynamic equilibrium calculation, the chemical forms and transformation mechanism of the toxic elements (TEs) were investigated. Moreover, the risk level of toxic elements to underground environment was also studied in this paper. Results showed that Zn and Ni are thiophilic elements and favored to react with S to generate ZnS and NiS in the UCG pyrolysis stage. In the 900–1300 °C reduction ash, the toxic elements (Zn, Be, Ni, Ba, and U) in the residual speciation (F4) have the large percentage. For the oxidation residuals, Be and U are intimately related with the Fe–Si–Al–O–Be–U mineral system, and F exists in the form of CaF2 . According to the risk assessment code (RAC), the harmful degree of toxic elements to the underground environment decreases with rises of reaction temperature. When the reaction temperature reaches 1200 °C, the harmful degree of toxic elements to the underground environment is range in the Low risk, indicating that the underground residuals have reached the stability. The results can provide suggestions for future handing of the underground coal gasification residuals. Graphical abstract: Image 1 Highlights: The chemical speciation of toxic elements was studied. The existing forms of toxic elements were studied. The risk assessment code (RAC) was introduced to evaluate the risk level.